STRATEGI THE BOEING COMPANY DALAM MENGHADAPI PERSAINGAN DAGANG PRODUK B737 MAX DAN A320NEO PADA PASAR INDUSTRI PENERBANGAN SIPIL - Anjelli, Risfa; Retnaningsih, Umi Oktyari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2026)
High-technology firms such as Boeing strategically managed their operations to sustain dominance within a competitive global oligopolistic market. The emergence of Airbus in 1970 gradually weakened Boeing’s long-standing dominance, which had been perceived as monopolistic since 1917. Both companies operate in the aerospace and civil aviation industry and dominated the global market, competing most intensely in the narrowbody commercial aircraft segment. Against this backdrop, this study examined Boeing’s strategic responses to trade competition, focusing on the rivalry between the B737 MAX and Airbus’s A320neo in the global civil aviation market. This study adopted a qualitative case study approach and applied Michael Porter’s Competitive Advantage theory, particularly the differentiation-based generic strategy. The analysis was structured into three phases: differentiation as a competitive response, the risk of being stuck in the middle, and re-differentiation. Data were collected from secondary sources, including official reports from Boeing and Airbus, statements issued by Boeing’s management, and publications from regulatory and international institutions such as the Federal Aviation Administration (FAA), International Civil Aviation Organization (ICAO), International Civil Aviation Organization (IATA), and World Trade Organization (WTO). The findings revealed a substantial decline in Boeing’s competitive advantage following the crashes of Lion Air Flight 610 (2018) and Ethiopian Airlines Flight 302 (2019), both involving the B737 MAX. Boeing responded by pursuing a differentiation strategy through technological upgrades and quality improvements to the B737 MAX, including MCAS modifications and the installation of dual AOA sensors; enhanced regulatory compliance through the re-certification of the B737 MAX 7 to MAX 10 variants; reputation recovery via the Strengthening Safety and Quality Plan; and supply chain recovery by shifting from mass production to phased production, with output increasing from 38 to 42 aircraft by October 2025. Keywords: A320neo, B737 MAX, Competitive Advantage, Trade Competition